2015
DOI: 10.4097/kjae.2015.68.5.476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraoperative infusion of ketamine on remifentanil-induced hyperalgesia

Abstract: BackgroundOpioid induced hyperalgesia (OIH) is related with high opioid dosage, a long duration of opioid administration, and abrupt discontinuation of infused opioids in anesthetic settings. Ketamine is known to attenuate OIH efficiently, but methods of administration and methods to quantify and assess a decrease in OIH vary. We demonstrated the existence of remifentanil-induced hyperalgesia and investigated the ability of ketamine to attenuate OIH.MethodsSeventy-five patients undergoing laparoscopic gynecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 29 publications
1
38
1
Order By: Relevance
“…35 All trials administered opioids before surgical incision. The administered dose ratio between lowand high-dose groups were respectively 1:15 in one trial, 27 between 1:8 and 1:6 in five trials, 29,34,37,41,52 between 1:5 and 1:2 in 18 trials 26,28,[31][32][33]35,36,[38][39][40]42,43,[46][47][48][49][50][51] and at a ratio of 1:1.5 in three trials. 30,44,45 Of note, one trial administered dose that are beyond what is commonly used in the clinical practice.…”
Section: Re Sultsmentioning
confidence: 99%
See 3 more Smart Citations
“…35 All trials administered opioids before surgical incision. The administered dose ratio between lowand high-dose groups were respectively 1:15 in one trial, 27 between 1:8 and 1:6 in five trials, 29,34,37,41,52 between 1:5 and 1:2 in 18 trials 26,28,[31][32][33]35,36,[38][39][40]42,43,[46][47][48][49][50][51] and at a ratio of 1:1.5 in three trials. 30,44,45 Of note, one trial administered dose that are beyond what is commonly used in the clinical practice.…”
Section: Re Sultsmentioning
confidence: 99%
“…35 No trials injected long-acting opioids such as morphine or hydromorphone at the end of surgery. Over 60% (18 of 27) of the included trials used a volatile-based anaesthesia maintenance, [26][27][28][29][33][34][35][37][38][39][40][41][42]44,46,48,50 while the remaining trials administered propofol. [30][31][32]36,43,45,47,49,51,52 Regarding the types of surgery, authors included patients scheduled for gynaecological surgery in seven trials, [27][28][29][30]35,42,44 for abdominal surgery in nine trials, 33,34,[37][38][39]41,43,49,50 for cardiac surgery in four trials, 31,32,45,51 and finally, we combined the remaining seven tr...…”
Section: Re Sultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many experimental studies have been published in this field. Some studies suggested that N-methyl-D-aspartate (NMDA) receptor antagonists such as ketamine may play a role as a useful adjuvant to reduce RIH (6)(7)(8). COX-2 inhibitor parecoxib which were also investigated as nonsteroidal anti-inflammatory drugs were often administered as premedication before surgery (9,10).…”
Section: Introductionmentioning
confidence: 99%